Diabetes Mellitus and Oral Health - H. Poskerová; P. Bořilová Linhartová; J. Vokurka; A. Fassmann; L. Izakovičová Hollá (Czech Dental Chamber, 2014)
Background: This review summarizes the current state of knowledge about the relationship between diabetes mellitus (DM) and diseases of the oral cavity tissues. In the introduction, the authors define diabetes including its classification, describe causes of DM origin as well as complications accompanying this disease. Further, the actual epidemiological data related to the diabetes occurrence in the Czech Republic and in the world are given. The authors summarize manifestation of DM in the oral cavity and its impact on the periodontal tissues (gingivitis and periodontitis), caries rate, state of the oral mucosa (oral candidiasis, oral lichen planus, atrophic glossitis, stomatodynia, glossodynia), state of the salivary glands (diabetic sialoadenosis), saliva formation, perception of taste stimuli and healing wounds in the oral cavity (extraction and other surgical treatments). The authors also explain in what manner and by which mechanisms the oral cavity tissues in DM patients are affected. The long-term increased blood glucose level leading to the origin of advanced glycation end products (AGEs) is considered as the main etiologic factor. These products together with other pathogenetic mechanisms (e.g. oxidative stress, polyol accumulation) lead to structural and functional alterations of capillaries, changes in collagen metabolism, functional changes of the immune cells, and bone metabolism. Study also shows a mutual relationship between DM and periodontitis and the effect of the periodontal treatment on this metabolic disease. The authors also consider effective prevention and insufficient motivation of diabetic patients for oral health care. In conclusion, results of the 9th European Workshop in Periodontology, which was held in Spain in autumn 2012 and focused on the relationship between periodontitis and systemic diseases, are mentioned together with the reference to the online proceedings of this conference where free full texts of all presented communications are available.